Educational Status of Muslim Women: A Sociological Analysis of Kundhar, Pokhara, Kaski - Bhusal, Shanti (Himalayan Journal of Sociology and Anthropology, 2014)
This research analyses the educational status of Muslim women aged between 16-40 years of Kundhar area that lies in ward numbers 10 12 and 13Pokhara sub metropolitan Kaski. A total of 60 Muslim women aged between 16-40 years were purposively selected as respondents. It primarily focuses on the participation of the women in education and the obstacles they face in attaining it. Marriage and religious beliefs have been found as the main factors hindering educational achievement for these women. These factors have limited the role of many respondents to being a house wife only. DOI: http://dx.doi.org/10.3126/hjsa.v6i0.10718 Himalayan Journal of Sociology and Anthropology Vol.6 2014: 203-210